2006
DOI: 10.1007/s10384-005-0320-y
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma in Taiwan: Survival Rate and Prognostic Factors

Abstract: The mortality rate of patients with retinoblastoma is higher in Taiwan than in developed countries. The proportion of patients' parents refusing or delaying treatment in Taiwan is high. The factors for a poor prognosis were an interval between onset and treatment of >5 months, a lag time before treatment of >2.5 months, and extraocular disease. The duration of symptoms was not a prognostic factor. The only independent factor indicating a poor prognosis was extraocular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
47
4
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 11 publications
14
47
4
3
Order By: Relevance
“…In the present study, the mean age at diagnosis of Rb was 24.5 months, which was similar to that reported in other developing countries and regions (24-28.5 months) (9)(10)(11)20) and in between the mean age in developed countries (19.7 months) (17) and less developed countries (36.5 months) (23) . Navo et al (20) found that death could be maximally avoided in younger Rb patients with less lag time before treatment if the patients were diagnosed early.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the mean age at diagnosis of Rb was 24.5 months, which was similar to that reported in other developing countries and regions (24-28.5 months) (9)(10)(11)20) and in between the mean age in developed countries (19.7 months) (17) and less developed countries (36.5 months) (23) . Navo et al (20) found that death could be maximally avoided in younger Rb patients with less lag time before treatment if the patients were diagnosed early.…”
Section: Discussionsupporting
confidence: 90%
“…3,4,5,6 However, in developing countries, the majority of patients with retinoblastoma present with advanced disease with the resultant 5 year survival of less than 50%. 7,8,9 The factors for this poor prognosis may include late presentation with a high mean age at diagnosis, 10,11 interval between onset and treatment of more than 5 months, a lag time before treatment exceeding 2.5 months, extraocular disease, 12 higher occurrence of poorly differentiated tumours, 13 presence of other histopathological high risk features (HHRF) for metastasis, and other factors such as lack of knowledge about the disease and its outcome, high costs of hospital care (diagnosis and treatment), and lack of resources for care. Improvement in survival in developing countries will require measures that enhance early reporting through health education, 14 early and cheaper means of screening those at risk and early diagnosis of affected patients, as well as early, affordable and effective forms of treatment including means of funding such as national health insurance or government-funded schemes.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, median age of presentation was 24 months which is comparable with previous other studies from North India (29 months), Iran (28.5 months), Taiwan (26.3 months) and Malaysia (24.2 months). 15,20,21 A relatively higher median age at diagnosis has been reported from African countries like Ghana (36 months) and Kenya (37.5 months). 14,22 Tumours were relatively diagnosed at an earlier age in Australia and USA.…”
Section: Discussionmentioning
confidence: 97%
“…12 Stage of the disease had a significant impact on the survival outcomes, which is consistent with previous studies that reported an association between severity of disease and the survival outcome. 21,33,34 The most feared complication of chemotherapy is the risk of developing other tumors in the medium and long term, particularly leukemia by use of Etoposide. 35 Radiation appears to have a higher incidence of non-ocular tumours.…”
Section: Discussionmentioning
confidence: 99%